Blending of Fiction with Historical Reality in Salman Rushdie’s Midnight’s Children and Grabiel Gracia Marquez’s One Hundred Years of Solitude - Sharma, Khum Prasad (Literary Studies, 2021)
This paper investigates the use of magic realism as a strategic tool in Salman Rushdie’s Midnight’s Children (1981) and Gabriel Garcia Marquez’s One Hundred Years of Solitude (1967). Both the authors belong to two distinct continents; still, they have similar histories and stories of struggle. They develop a unique relationship while untangling reality. They create the mysterious relationship between the human beings and their circumstances in a way more realistic than the realist text.Also, the textual analysis reveals the basic goal of both the novelist to revisit their past through magic realism as both of them believe in the distortion of reality as outcome of colonial impact in their respective societies. In this sense, this paper justifies the rationale behind the blending of fiction and historical reality in both the novels. In doing so it explores how the unsayable in today’s world of asymmetrical power and domination could be said through the use of tools and elements of magic realism such as hybridity, authorial presence, metafiction, awareness of mystery in a real world setting.